2017
DOI: 10.1109/jlt.2016.2628092
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-Core Microstructured Optical Fiber Gas Sensors

Abstract: Recent progress in gas detection with hollow-core microstructured optical fibers (HC-MOFs) and direct absorption/photothermal interferometry spectroscopy are reported. For direct-absorption sensors, the issue of mode interference noise is addressed and techniques to minimize such a noise are experimentally demonstrated. Large-scale drilling of hundreds of low-loss micro-channels along a single HC-MOF is demonstrated, which reduces the diffusion-limited response time from hours to ~40 seconds for sensing HC-MOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 94 publications
0
51
0
Order By: Relevance
“…However, it is hard to fill gas into the long and thin hollow core from the fiber ends, even with the help of a pressure differential. Drilling side holes through the cross section of the fiber reduces gas filling time, but it also compromises the mechanical robustness of the fiber and introduces additional propagation loss [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is hard to fill gas into the long and thin hollow core from the fiber ends, even with the help of a pressure differential. Drilling side holes through the cross section of the fiber reduces gas filling time, but it also compromises the mechanical robustness of the fiber and introduces additional propagation loss [13].…”
Section: Introductionmentioning
confidence: 99%
“…Labelfree We demonstrated distributed hydrogen sensing over a 100-m-long HC-PCF with microchannels drilled over a length of 2.2 m. It is feasible to fabricate a large number of microchannels along the entire length of the HC-PCF for real time distributed gas detection. With a femtosecond laser, we have demonstrated the fabrication of hundreds of micro-channels with an average loss below 0.01 dB per channel [27]. Observation of the fabrication process showed that most of the micro-channels have negligible contribution to the fiber loss and a few poorly made micro-channels raised the level of the average loss, which is believed caused by the scrap generated during the femtosecond laser drilling process.…”
Section: Techniquementioning
confidence: 98%
“…For the purpose of gas ingress/egress, 56 pairs of micro-channels (i.e., 112 micro-channels) were drilled over a 2.2-m region around the location 88 m along the 100-m-long sensing HC-PCF. The drilling was done with an 800-nm femtosecond laser micro-machining system [27]. The separation between the adjacent pairs of micro-channels is ~4 cm, and the spacing between the two channels forming a pair is 200 µm.…”
Section: Appendix D: Hc-pcf Sample Preparationmentioning
confidence: 99%
“…Here, we first summarize the synthetic strategies of hollow MOFs and their derivatives. Afterward, we discuss their morphological and compositional effects on the applications in catalysis, gas sensors, batteries, supercapacitors, electrocatalysis, and others . Armed with discussions with several representative examples, the design and preparation strategies of hollow MOFs and their derivatives are clarified.…”
Section: Introductionmentioning
confidence: 99%